1966
DOI: 10.1021/ja00956a018
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemistry of Inorganic Difluoramino Compounds. II. Solution Chemistry and Electrochemical Reduction of Difluoramine

Abstract: The mechanism of the electrochemical reduction of difluoramine has been studied in water, protonic organic solvents, and aprotic solvents. In water and protonic solvents, such as alcohols, difluoramine undergoes a diffusion-controlled, four-electron reduction to ammonia. In aprotic solvents, such as acetonitrile and dimethyl sulfoxide, the reduction product is ammonia, but the reaction is not completely diffusion controlled. In these systems, ammonia is formed by reaction of the electrode products with the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…From these facts it can be concluded that the first mechanism is more probable. That mechanism resembles the one proposed by Ward et al 21 for NHF 2 reduction on a mercury electrode.…”
Section: ͓27͔supporting
confidence: 87%
“…From these facts it can be concluded that the first mechanism is more probable. That mechanism resembles the one proposed by Ward et al 21 for NHF 2 reduction on a mercury electrode.…”
Section: ͓27͔supporting
confidence: 87%
“…Polarographic behavior of difluoramine, HNF2, was measured in water and protonic solvents (1391) and the technique was used to detect the difluoroamide anion, NF2~(855). The hydrogen wave was measured in presence of weak bases (1126).…”
Section: Organic Halogenmentioning
confidence: 99%